The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/cells11152432
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptors and the Hallmarks of Cancer

Abstract: Peroxisome proliferator-activated receptors (PPARs) function as nuclear transcription factors upon the binding of physiological or pharmacological ligands and heterodimerization with retinoic X receptors. Physiological ligands include fatty acids and fatty-acid-derived compounds with low specificity for the different PPAR subtypes (alpha, beta/delta, and gamma). For each of the PPAR subtypes, specific pharmacological agonists and antagonists, as well as pan-agonists, are available. In agreement with their natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 511 publications
0
25
0
Order By: Relevance
“…PPAR-γ is frequently expressed in various cancer cells, including breast, lung, colon, lips, kidney, pancreatic and thyroid [ 32 ]. Several studies have revealed that PPAR-γ activation by its agonists imposes cell cycle arrest [ 33 ], apoptosis [ 34 ], angiogenesis [ 35 ], inhibition [ 36 ], and redifferentiation [ 37 ], which are the key molecular processes associated with the prevention of tumor growth and progression. The expression of angiogenesis-related proteins such as vascular endothelial growth factor (VEGF) and cyclooxygenase-2 as well as inflammatory mediators in the tumor microenvironment are all inhibited by PPAR-γ activation [ 38 ].…”
Section: Functional Diversity Of Ppar-γmentioning
confidence: 99%
See 1 more Smart Citation
“…PPAR-γ is frequently expressed in various cancer cells, including breast, lung, colon, lips, kidney, pancreatic and thyroid [ 32 ]. Several studies have revealed that PPAR-γ activation by its agonists imposes cell cycle arrest [ 33 ], apoptosis [ 34 ], angiogenesis [ 35 ], inhibition [ 36 ], and redifferentiation [ 37 ], which are the key molecular processes associated with the prevention of tumor growth and progression. The expression of angiogenesis-related proteins such as vascular endothelial growth factor (VEGF) and cyclooxygenase-2 as well as inflammatory mediators in the tumor microenvironment are all inhibited by PPAR-γ activation [ 38 ].…”
Section: Functional Diversity Of Ppar-γmentioning
confidence: 99%
“…They are considered as weak activators of PPAR-γ compared with full agonists, which shows lower transactivation potential and imparts desirable effect [ 69 ]. Agonist-mediated activation of PPAR-γ has been reported to exhibit anti-inflammatory properties, growth inhibitory effects and prevent proliferation of many human cancer cell lines [ 34 , 64 ]. Likewise, the antagonist activity has also been observed to destabilize H12 and stabilize H3 and β-sheet.…”
Section: Ppar-γ Activation By Various Ligandsmentioning
confidence: 99%
“…The close interplay between lipid oxidation, chronic inflammation, and cancer [ 16 ] oriented the researchers to also explore the antitumor activity of PPAR ligands, leading to a significant amount of literature data, sometimes reporting contrasting results. In fact, PPAR isoforms can function as tumor suppressors or inducers, depending on the biological context and the cancer type [ 17 , 18 ]. A remarkable attention has been paid to PPARα antagonists, whose activity on fatty acid metabolism could be responsible for a metabolic alteration of cancer cells, by promoting a switching from glycolysis to fatty acid oxidation [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…PPARs belong to the group of nuclear receptors that activate or repress target genes as heterodimers with retinoic X receptors (RxR). PPARs family included: PPAR alpha (PPARα), PPAR beta/delta (PPARβ/δ), and PPAR gamma (PPARγ) [ 32 ]. Different types of cells exhibited various expressions of PPARs; thus, the outcome of its activation might be different in various tissues [ 33 ].…”
Section: Introductionmentioning
confidence: 99%